Evaluation Of A Two Stroke Compressed Natural Gas Mixer Design By Simulation And Experimental Techniques - D., Ramasamy; Samykano, Mahendran (2010)

(untitled)
Natural gas is a viable alternative fuel that is able to reduce tailpipe emission, most notably in two stroke engines it is available in compressed form or Compressed Natural Gas (CNG) for easy storage. The excessive by-products of two-stroke engine combustion; normally due to inefficient combustion process is largely attributed to high particulate, carbon monoxide and hydrocarbon constituents. A prototype uniflow-type single-cylinder engine was equipped with a bi-fuel conversion system were used for the work. A dedicated mixer was also developed to meter the gaseous fuel through the engine intake system. It was designed to meet the air and fuel requirement similar to the gasoline counterpart. Modeling of the mixer was made to obtain optimum orifice diameter using three different sizes of 14, 16 and 18mm respectively. Here, flow simulations using a standard Computational Fluid Dynamics (CFD) software were extensively used and the predicted results were subsequently validated using a dedicated a flow test rig. Pressure drop across the venturi is an important parameter as it determines the actual fuel-air ratio in the actual engine. A good agreement of CFD outputs with that of the experimental outputs was recorded. This paper highlights the work, which leads to the use of the dedicated CNG fuelling system in a general-purpose gasoline two-stroke engine.